2005
DOI: 10.1097/01.mlg.0000154735.61775.cd
|View full text |Cite
|
Sign up to set email alerts
|

Facial Nerve Dysfunction After Parotidectomy: The Role of Local Factors

Abstract: In the study series of conservative parotidectomies with facial nerve dissection, only extent of surgery and particular local conditions of nerve dissection, especially the close contact of tumor with facial nerve and inflammatory conditions, were found to be associated with postoperative facial nerve dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
5
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 14 publications
8
103
5
6
Order By: Relevance
“…The branch of the facial nerve most at risk for injury during parotidectomy is the marginal mandibular branch. 12 In our study, we found five (45.46%) patients had marginal mandibular injury. So the result is comparable with the above study.…”
Section: Discussionmentioning
confidence: 48%
“…The branch of the facial nerve most at risk for injury during parotidectomy is the marginal mandibular branch. 12 In our study, we found five (45.46%) patients had marginal mandibular injury. So the result is comparable with the above study.…”
Section: Discussionmentioning
confidence: 48%
“…Although a large percentage of these recover, the short-term and unfortunately some longterm palsies can have profound impacts on a patient's quality of life especially in the setting of an apparent small and innocuous lesion [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The marginal mandibular branch was reported as the single most affected nerve branch following parotidectomy (48.2 %). Facial nerve dysfunction after total parotidectomy was found to be significantly higher (P \ 0.001) than that in superficial parotidectomy (18.2 % at day 1 and 10.9 % at month 1) [3].…”
Section: Discussionmentioning
confidence: 83%